Analysis of Content Engagement Rate on Wicida Tv's Instagram Account - Vania Diva Az-zira; Ita Arfyanti; Hanifah Ekawati (Poltanesa, 2026)
Wicida Tvis one of the UKM (Student Activity Units) at STMIK Widya Cipta Dharma. The UKM has various social media and in this study the Wicida TvInstagram account was chosen, which aims to analyze the level of interaction with followers and other users on the content published on the Wicida Tv’s Instagram account. By using a mix method approach, with a focus on quantitative calculations for engagement rate results and qualitative methods are used to support the results of quantitative calculations. Data was collected based on Instagram content both photos, video viewers, reels, and posters uploaded in the last 1 year period (2025), in collecting engagement rate data not only using the number of likes, comments, shares, and reposts, but also can be taken by measuring how often people click on the link and bio in the post as well as the distribution of questionnaires which will later be processed using SPSS tools. The results of the analysis show that the engagement rate of the content on the Wicida TvInstagram account on average has an average engagement rate that can be said to be quite good. And while users are generally more interested in entertainment content than formal educational content, factors such as upload time and creativity have been shown to influence user engagement levels. This research provides insights for social media account managers in improving content strategies to achieve optimal follower engagement.